Layers of intervention for revitalization of historical districts - Hossein, Norouzi; Zienab, Rabiee; Ensieh, Ghavampour; Seyyed Amir, Mansoori (2008)

(untitled)
The historical context of a city is part of its physical body, the existence of which has begun in the far past and is now challenging and opposing modern urban developments. Today, in the process of making optimum use of urban lands, treating the historical contexts has turned into a dilemma, for with such blocks being of vast areas, it is impossible for them to be frozen and turn into museums; on the other hand, it’s impossible to halt the process of developing new buildings, the visual and historical properties of which do not match the ones of the old context. Now the question, in studies regarding the revitalization of ancient, historical contexts is: how can the paradox of modern life and its needs be combined with the old urban context? ‘Oudlaajaan, a neighborhood in the west of Tehran, was built during Safavid Dynasty and is now, due to wrong policies applied by urban management authorities during different eras, worn in many aspects. With the inhabitants not feeling to belong in the place and the presence of functions which do not match the physical body, the area has completely lost its visual values. In case we want to perform a more realistic and effective revitalization, it’s better to view the historical context, not as a combination of building blocks, but as a system. In this article, we tend to present four layers of action to revitalize ancient contexts. It’s necessary for planners of urban policies to legislate and make their decisions in each one of these layers, and through the hierarchy mentioned that will be mentioned.